Termination of non-coding transcription in yeast relies on both an RNA Pol II CTD interaction domain and a CTD-mimicking region in Sen1 - Han, Zhong; Jasnovidova, Olga; Haidara, Nouhou; Tudek, Agnieszka; Kubicek, Karel; Libri, Domenico; Stefl, Richard; Porrua, Odil (The EMBO journal, 2020)
Pervasive transcription is a widespread phenomenon leading to the production of a plethora of non-coding RNAs (ncRNAs) without apparent function. Pervasive transcription poses a threat to proper gene expression that needs to be controlled. In yeast, the highly conserved helicase Sen1 restricts pervasive transcription by inducing termination of non-coding transcription. However, the mechanisms underlying the specific function of Sen1 at ncRNAs are poorly understood. Here, we identify a motif in an intrinsically disordered region of Sen1 that mimics the phosphorylated carboxy-terminal domain (CTD) of RNA polymerase II, and structurally characterize its recognition by the CTD-interacting domain of Nrd1, an RNA-binding protein that binds specific sequences in ncRNAs. In addition, we show that Sen1-dependent termination strictly requires CTD recognition by the N-terminal domain of Sen1. We provide evidence that the Sen1-CTD interaction does not promote initial Sen1 recruitment, but rather enhances Sen1 capacity to induce the release of paused RNAPII from the DNA. Our results shed light on the network of protein-protein interactions that control termination of non-coding transcription by Sen1.
Keywords: transcription termination; Transcription Termination, Genetic; RNA-helikasy; Saccharomyces cerevisiae Proteins; vazebná místa; RNA polymerase II CTD; RNA, Untranslated; Saccharomyces cerevisiae; vazba proteinů; proteiny vázající RNA; fungální RNA; proteinové domény; terminace genetické transkripce; DNA Helicases; Protein Domains; pervasive transcription; nekódující RNA; Models, Molecular; Protein Conformation; molekulární modely; non-coding transcription; Sen1 helicase; RNA-polymerasa II; RNA Helicases; Gene Expression Regulation, Fungal; RNA Polymerase II; konformace proteinů; RNA, Fungal; RNA-Binding Proteins; regulace genové exprese u hub; Saccharomyces cerevisiae - proteiny; DNA-helikasy; Protein Binding; Binding Sites